Abe's call to stand up to China : at what cost? - Ho, Benjamin (2014)
Japanese Prime Minister Shinzo Abe issued a siren call at the recent World Economic Forum in Davos that the world must stand up to an increasingly assertive China. Will this resonate with the broader international community, especially the business fraternity which has made strong inroad into Chinese society?